Design and Synthesis of Novel 2, 4‐Diamino‐5‐pyrazol‐4‐yl Pyrimidine Derivatives as Selective Tyro3 Kinase Inhibitors. (24th July 2018) - Kim, Dukwoon; Lee, Kyung Won; Jung, Hyunseok; Kim, Miok; Lee, Joo‐Youn; Lee, Yeonkyung; Hwang, Jong Yeon; Min, Youngki; Lee, Chang Hoon; Cho, Sung Yun
Abstract :